Kids' Birthday Party (Cottage Farm, Sywell : Igloo Books, 2016)
With delicious recipes to tickle your taste buds, Kids' Birthday Cakes shows you how to create fun novelty cakes, from pirate ships and princesses to volcanoes and trains!
Keywords: Birthday cakes; Cake decorating